New media in communication – challenges and needs - Bereźnicka, Małgorzata (Logopedia Silesiana, 2021)
The article delineates the changes that have taken place as a result of the use of new media, especially the Internet, in the context of the development of information and communication technologies, and describes the differences between classical communication and web contacts. The most common types of Internet threats and the ambiguous influence of online contacts on the social life of an individual are discussed. It is emphasised that new media have numerous advantages, but they can also cause risky situations, and therefore it is necessary to provide education in this area, especially (but not only) to young generations. Further multifaceted research is also recommended to enable the diagnosis of the changing reality and develop solutions to problems related to the use of information and communication technologies.